Direct Anterior Approach Versus Posterolateral Approach in Total Hip Arthroplasty: A Systematic Review and Meta‐analysis of Randomized Controlled Studies - Xian‐teng Yang; Hai‐feng Huang; Li Sun; Zhen Yang; Chao‐yong Deng; Xiao‐bin Tian (Orthopaedic Surgery, 2020)
Objective To compare the early rehabilitation effects of total hip arthroplasty (THA) with the direct anterior approach (DAA) versus the posterior approach (PA). Methods We searched PubMed, Embase, Web of Science, the Cochrane Library, and Google databases from inception to June 2019 to select studies that compared the DAA and PA for THA. Only randomized controlled trials (RCT) were included. Two researchers independently screened studies for inclusion, extracted data, and assessed the methodological quality. A meta‐analysis was conducted using RevMan 5.3 software provided by Cochrane Assisted Network. Results A total of 932 patients underwent THA. There were 467 cases in group DAA and 465 cases in group PA. There was a significant difference in the incidence of lateral femoral cutaneous nerve injury between DAA and PA groups (RR = 38.97, 95% CI: 7.89–192.57, P < 0.05). DAA was associated with less pain compared with PA [WMD = −0.65, 95% CI (−0.91–0.38), P < 0.05]. There was no significant difference in operation time, hospitalization stay, and intraoperative bleeding volume. Moreover, in supplementary data, the number of acetabular prostheses in Lewinnek's safety zones in DAA was more than that in the PA group (RR = 1.20, 95% CI [1.04–1.39], P < 0.05), and the time of discontinuation of walking aids in the DAA group was earlier than that in the PA group (WMD = −11.05, 95% CI [−17.79–4.31], P < 0.05). Conclusion The DAA total hip arthroplasty has comparable results with PA, with earlier postoperative functional recovery, less postoperative pain scores, and higher incidence of lateral femoral cutaneous nerve injury. The results need to be validated by large‐sample, high‐quality RCT studies, and long‐term follow‐up of complications.